Experimental demonstration of micro LED to micro LED visible light communication - Bo-Geun Kim; Min-Ho Son; Sung-Man Kim (ICT Express, 2024)
LED-to-LED visible light communication (VLC) is a technology that LEDs are used as both transmitters and receivers. In this paper, we studied a micro-LED-to-micro-LED VLC since micro LEDs have faster modulation speed and are used in various applications recently. The frequency responses and SNRs were measured for all possible combinations of four LED colors (red, green, blue, and white) in the transmitter and the receiver. Through this, the theoretical maximum channel capacity was estimated for each combination case. Finally, we conducted an experiment with the optimal transmitter and receiver LED set and investigated its performance.